Nature and formation of interlayer fillings in clay minerals in Albeluvisols from the Carpathian Foothills, Poland - Szymański, Wojciech; Skiba, Michał; Nikorych, Volodymyr A.; Kuligiewicz, Artur (Geoderma, 2014)
The occurrence of interlayer fillings in clay minerals in the slightly acidic soils of humid temperate zone is a very common and characteristic feature. According to the research literature, the interlayer fillings may be composed of mineral and/or organic materials. The formation of mineral-interlayered clay minerals in soils is related to weathering, which leads to the liberation of cations from the crystalline structure of soil minerals and their subsequent sorption and fixation as a hydroxyl sheet within interlayer spaces of swelling clay minerals, or it may be due to the weathering of chlorite and partial removal of the hydroxyl sheet from interlayer spaces. The formation of organic interlayering within clays is related to interactions between organic and mineral colloids occurring in soil environment. The main aim of the present study was to determine the nature and formation of the interlayer fillings in clay minerals in four Albeluvisols from the Carpathian Foothills in southern Poland showing the occurrence of a fragipan and various degrees of bleaching due to periodic stagnation of water as well as ongoing land use (i.e. forest soils vs. arable soils). This was done using research results obtained from X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR and FTIR-ATR), and chemical analysis. The obtained results show that Albeluvisols from the Carpathian Foothills in Poland are characterized by the occurrence of clay minerals with interlayer fillings, which are the most developed in the upper soil horizons (A, AE, and E). The nature of interlayer fillings in clay minerals in the Albeluvisols studied is mainly organic; however, an additional presence of very small amounts of metal-hydroxy polymers in the interlayer space of clays cannot be completely excluded. Clay minerals with interlayer organic fillings found in the upper soil horizons are formed from swelling clays (smectite and vermiculite) due to the accumulation of organic matter in the interlayers during pedogenesis. The same pattern of clay mineral transformation (i.e. swelling clays into interlayered clays) is observed in Albeluvisols showing strong bleaching and slight bleaching and subject to different forms of land use (i.e. forest soils vs. arable soils). Most likely, this is related to quite similar physical and chemical properties of the soils as well as similar environmental conditions (except of ongoing land use). Quantity of organic matter does not play a crucial role in the formation of organic interlayered clays in soil environment. The most important is low pH (below 5.5) of soil solution and the presence of expandable clay minerals in soil material. •Interlayer fillings in clay minerals in Albeluvisols were studied.•Nature of the interlayer fillings is mainly organic.•The organic interlayer fillings in clay minerals occur mainly in upper horizons.•The interlayered clay minerals are formed from swelling clays.